2022
DOI: 10.18549/pharmpract.2021.4.2559
|View full text |Cite
|
Sign up to set email alerts
|

What drives pharmacists’ turnover intention: A systematic review

Abstract: Background: Pharmacist turnover can negatively impact not only on work efficiency, organizational performance, work productivity and customer satisfaction, but also on the quality of pharmaceutical services and patient safety. Turnover intention is a core antecedent of turnover. Turnover intention of the pharmacists is affected by many factors related to their organization or job. Objective: To elaborate the factors affecting the pharmacists' turnover intention and their associations. Studies related to any fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Job stress and work climate, as well as burnout, poor public perception, and a lack of career progression, had direct and indirect effects on turnover intention of hospital pharmacists. 77,78 In a survey by the Royal Pharmaceutical Society (UK), 89% of pharmacists reported a high risk of burnout, 33% considered leaving their current role and 32% thought about leaving the profession altogether. 79 There is an irreconcilable conflict here, given a motivation driving people to pursue a career in the pharmacy profession is the willingness to help people, and pharmacists will often choose to 'do more' sometimes at the expense of their own wellbeing.…”
Section: Summary Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Job stress and work climate, as well as burnout, poor public perception, and a lack of career progression, had direct and indirect effects on turnover intention of hospital pharmacists. 77,78 In a survey by the Royal Pharmaceutical Society (UK), 89% of pharmacists reported a high risk of burnout, 33% considered leaving their current role and 32% thought about leaving the profession altogether. 79 There is an irreconcilable conflict here, given a motivation driving people to pursue a career in the pharmacy profession is the willingness to help people, and pharmacists will often choose to 'do more' sometimes at the expense of their own wellbeing.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Many studies have reported that organisational commitment and job satisfaction had a significant influence on pharmacist turnover intention in all settings. Job stress and work climate, as well as burnout, poor public perception, and a lack of career progression, had direct and indirect effects on turnover intention of hospital pharmacists 77, 78 . In a survey by the Royal Pharmaceutical Society (UK), 89% of pharmacists reported a high risk of burnout, 33% considered leaving their current role and 32% thought about leaving the profession altogether 79…”
Section: Theme 6 — Workforce Wellbeingmentioning
confidence: 99%
“…To reduce pharmacists’ turnover and change their turnover behavior, it is crucial for managers to learn about the factors that significantly influence turnover intention. 8 …”
Section: Introductionmentioning
confidence: 99%
“…According to the current research, perceived organizational support is significantly related to turnover intention. 8 , 9 Eisenberger et al first developed the term “perceived organizational support”. It refers to the employees’ overall feelings and beliefs about how the organization views their contribution and cares about their interests.…”
Section: Introductionmentioning
confidence: 99%
“…Losing an employee can obstruct a pharmacy industrial company -not only regarding the expenses of changing and educating the modernday employee -however, within the facts, records, and relationships that may be lost at the same time as an individual chooses to move away and exchange jobs. [5][6][7] The theories that describe work satisfaction serve as a foundation for identifying the numerous elements that affect job satisfaction and provide suggestions for how to raise employee job satisfaction. The Herzberg Motivator-Hygiene Theory 8 is among these hypotheses.…”
mentioning
confidence: 99%